Multi-Criteria Decision-Making Approach in Personnel Selection Problem - A Case Study at the University of Pardubice - Gottwald, Dalibor; Jovčić, Stefan; Lejsková, Pavla (Academy of Economic Studies, 2022)
Nowadays, the personnel selection problem represents one of the crucial issues of any organization dealing with business activities. By employing the right person in the company, it means a lot for that company. Some of the benefits are increased profit, reduced costs, satisfied clients, a better working environment, relationships among people, etc. This article discusses the personnel selection problem at the University of Pardubice. To select the best possible PhD candidate for this educational institution, multi-criteria decision-making methods are being used. The combination of the two methods is used. The first one is the ARAS method, used to obtain the preferences of the PhD candidates. The results discussed.
Vícekriteriální rozhodování při výběru zaměstnanců - případová studie na Univerzitě v Pardubicích
Keywords: multi-criteria decision-making; entropy; ARAS; entropy-ARAS method; personnel selection; vícekriteriální rozhodování; entropie; ARAS; výběr zaměstnanců; entropie-ARAS